Formation of the criminal law of the Republic of Kazakhstan on the responsibility for compulsion to perform sexual acts - Biebayeva, А.А.; Kalguzhinova, А.M.; Mavlianov, A.S. (KSU publ, 2015)
The article is devoted to the historical and legal review of the regulation of criminal liability for compulsion to perform sexual acts. Studying the historical development and improvement of criminal law provision, authors mark the basic legislative acts adopted during the certain periods of development of domestic legislation, considering their features. Analysis of changes and amendments to the Criminal Code the Republic of Kazakhstan, includes theoretical underpinning of the new laws of recent years.
Keywords: compulsion to perform sexual acts; history of the criminal law of the Republic of Kazakhstan; Kazakh customary law; Russian criminal law; Soviet criminal law; Criminal Code of the republic of Kazakhstan of 1997; punishment for compulsion to perform sexual acts